Geological and ecological preconditions for the development of hydrogelological "windows" (by example of cretaceous water intakes in Eastern Ukraine) - Кононенко, А. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2018)
Formulation of the problem. The article describes geological and ecological preconditions for the development of hydrogeological "windows" in the waterproof strata of the marl-chalk aquifer. Hydrogeological "windows", in some cases, can serve as conductors of pollutants in groundwater. This particular feature is one of the main factors that impair the quality of drinking groundwater. The task of hydrogeologists is to determine the location of hydrogeological "windows", establishing the geological preconditions for their development. The purpose of the article is to define and characterize geological and ecological preconditions of hydrogeological "windows" development in the waterproof strata of the marl-chalk aquifer in cretaceous water intakes in Eastern Ukraine. Methods. The studies presented in this article were carried out in accordance with the methodology of ecological and hydrogeological study of the territories conditions and the methodology for assessing the ecological status of the territories. Results. Investigation of geological and ecological preconditions in hydrogeological "windows" development is shown on the example of some of the largest cretaceous water intakes in Eastern Ukraine – Svitlychansky, Zhytlivsky and on the complex of marl-chalk water intakes in Kharkiv region. The article analyzes geological, hydrogeological, tectonic, geomorphological and paleogeographic features in the structure of the study area. On the basis of these data, geological preconditions of hydrogeological "windows" development on the investigated territory have been established: crossing the river valleys of tectonic structures; presence of local increase sites of groundwater mineralization near zones of tectonic disturbances; development of tectonic disturbances zones with their operating fracture zones; exit of cretaceous to the daytime surface. Scientific novelty and practical significance. The conditions for hydrogeological "windows" formation are given and grounded. Systematic signs of hydrogeological "windows" existence and practical classification of hydrogeological "windows" is proposed. The environmental consequences of their existence are presented.